Development of cotton-rich/polylactic acid fiber blend knitted fabrics for sports textiles. (November 2015) - Guruprasad, R; Vivekanandan, MV; Arputharaj, A; Saxena, S; Chattopadhyay, SK
In this study, the moisture and thermal transmission properties of cotton/polylactic acid-blended knitted fabrics were studied. Cotton and polylactic acid fibers were blended to produce yarns of 14.7 tex (40 s Ne) with two different blend proportions. The yarns were then knitted into plain jersey structures, followed by scouring and bleaching treatments. The produced fabrics were evaluated for dynamic moisture transport properties using SDL Atlas moisture management tester. The moisture vapor transmission rate of developed fabrics was measured using the dish method, and the thermal properties were measured using KES Thermolabo instrument. Results indicate that blending of polylactic acid fibers with cotton fibers improve the moisture management properties of the resultant fabric. The overall moisture management capability values were found to be better for cotton/polylactic acid fiber 65:35 blended fabric. A marginal improvement was observed only in the case of cotton/polylactic acid fiber 80:20 blended fabric. The moisture vapor transmission and air permeability of blended fabrics were also found to be higher than those of 100% cotton fabric. The thermal conductivity, insulation, and warm–cool feel values of blended fabrics range between 100% cotton and 100% polylactic acid fiber fabrics. This type of fabric is more suitable for use as sportswear and active wear.